How would you put this expression in factored form? 4x2 + 11x + 6

Answers

Answer 1
Answer:

we have

4x^(2) +11x+6

Equate the expression to zero

4x^(2) +11x+6=0

Group terms that contain the same variable, and move the constant to the opposite side of the equation

4x^(2) +11x=-6

Factor the leading coefficient

4(x^(2) +(11x/4))=-6

Complete the square. Remember to balance the equation by adding the same constants to each side

4(x^(2) +(11x/4)+(121/64))=-6+(121/16)

4(x^(2) +(11x/4)+(121/64))=(25/16)

(x^(2) +(11x/4)+(121/64))=(25/64)

Rewrite as perfect squares

(x+(11/8))^(2)=(25/64)

Square root both sides

x+(11/8)=(+/-)\sqrt{(25)/(64)}

x=(-11/8)(+/-)(5)/(8)

x=(-11/8)+(5)/(8)=-(6)/(8)=-(3)/(4)

x=(-11/8)-(5)/(8)=-(16)/(8)=-2

therefore

4x^(2) +11x+6=4(x+(3)/(4))(x+2)=(4x+3)((x+2)

the answer is

(4x+3)((x+2)

Answer 2
Answer:

Answer:

Its (4x+3)(x+2) 100%

Step-by-step explanation:



Related Questions

Please Help Will Give Brainliest If Correct!The line segment shown is rotated 90° about the origin (counterclockwise). What are the new coordinates of point A?A) (2, 1) B) (-2, 1) C) (-2, -1) D) (1, 2)
Match the vocabulary word to its correct definition. 1. additive inverse a number belonging to the set made up of the whole numbers and their opposites 2. integer 4 a number belonging to the set made up of zero and the natural numbers 3. irrational number the opposite or negative of a number; the sum of a number and its additive inverse is zero 4. natural number a number belonging to the set made up of the numbers that are used to count: 1, 2, 3, and so on 5. rational number a number that can be written as a ratio of two integers in the form a/b with b ≠ 0 6. whole number a number that cannot be written as a ratio of two integers, which has an infinite decimal representation that does not repeat
Draw a quick picture for 37 . Draw to show how you would subtract 19 from 37 write to explain what you did
0.0259 in scientific notation
Please help if you know how to solve itThank you!

Find the product.(2p + 7)(3p - 9)
6p2 - 3p - 63
6p2 + 3p - 63
6p2 + 39p - 63
6p2 + 3p - 2

Answers

(2p + 7)(3p-9)
2p x 3p= 6p^2
2p x -9= -18p
7 x 3p=21p
7 x -9=-63
6p^2 - 18p + 21p - 63
6p^2 + 3p -63 is the answer.
If you would like to solve (2 * p + 7) * (3 * p - 9), you can calculate this using the following steps:

(2 * p + 7) * (3 * p - 9) = 2 * p * 3 * p - 2 * p * 9 + 7 * 3 * p - 7 * 9 = 6 * p^2 - 18 * p + 21 * p - 63 = 6 * p^2 + 3 * p - 63

The correct result would be 6 * p^2 + 3 * p - 63.

Cutting a 4 foot ribbon into 7 equal parts, how long is each piece

Answers

The length of each piece will be 4/7 or 0.57
each piece would be 6.86 inches long.
pretty short must have ment the person had short hair :)

What is the sum of the given polynomials in standard form?
(x2 – 3x) + (–2x2 + 5x – 3)

Answers

Answer:

-x^2+2x-3

Step-by-step explanation:

We have (x^2- 3x) + (-2x^2 + 5x -3) which is the same as:

x^2-3x-2x^2+5x-3

The polynomial has 5 terms that we are going to analyse:

1st. term: x^2       Degree: 2   Coefficient: 1

Observation: Coefficient is the number in front of a variable. In this case the variable is x. Then the first term has coefficient 1 because (1).x^2=x^2.

2nd. term: -3x     Degree:1     Coefficient: (-3)

3rd. term: -2x^2  Degree:2    Coefficient: (-2)

4th. term: 5x      Degree:1     Coefficient: 5

5th. term: -3        Degree:0    Coefficient: (-3)

We have to reorder the polynomial writing each term in order of degree from highest to lowest (left to right).

The terms with highest degree are the first and third. Then the second and fourth term. And the lowest degree  corresponds to the fifth term.

The polynomial now is:

x^2-2x^2-3x+5x-3

Now we have to sum the terms that have the same degree:

x^2-2x^2=(1-2)x^2=(-1)x^2=-x^2

-3x+5x=(-3+5)x=2x

Then the result is:

-x^2+2x-3

-x2 + 2x - 3 is the final answer to that

Simplify the expression:
25 - 3(5x - 6) - 22x

Answers

Answer:

yup

Step-by-step explanation:

Simplify 4x + 8 + 2x - 7.

Answers

Answer:

6x+1

Step-by-step explanation:

hope this helps

17. Find all the real fourth roots of 0.0001.

Answers


3. 0.1778, -0.1778 Are you sure that you don't mean the fourth root of 0.0001?That would be 0.1, -0.1